Out of the Qinghai‐Tibet plateau: Genomic biogeography of the alpine monospecific genus Megadenia (Biscutelleae, Brassicaceae). Issue 2 (27th November 2022) - Yang, Wenjie; Feng, Landi; Jiao, Pengfei; Xiang, Ling; Yang, Luobai; Olonova, Marina V.; Chepinoga, Victor V.; Al‐Shehbaz, Ihsan A.; Liu, Jianquan; Hu, Quanjun
Abstract: Numerous high‐elevation alpine plants of the Qinghai‐Tibet Plateau (QTP) also have disjunct distribution in adjacent low‐altitude mountains. The out‐of‐QTP versus into‐the‐QTP hypothesis of alpine plants provide strong evidence for the highly disputed assumption of the massive ice sheet developed in the central plateau during the Last Glacial Maximum (LGM). In this study, we sequenced the genomes of most known populations of Megadenia, a monospecific alpine genus of Brassicaceae distributed primarily in the QTP, though rarely found in adjacent low‐elevation mountains of north China and Russia (NC‐R). All sequenced samples clustered into four geographic genetic groups: one pair was in the QTP and another was in NC‐R. The latter pair is nested within the former, and these findings support the out‐of‐QTP hypothesis. Dating the four genetic groups and niche distribution suggested that Megadenia migrated out of the QTP to adjacent regions during the LGM. The NC‐R group showed a decrease in the effective population sizes. In addition, the genes with high genetic divergences in the QTP group were mainly involved in habitat adaptations during low‐altitude colonization. These findings reject the hypothesis of development massive ice sheets, and support glacial survival of alpine plants within, as well as further migration out of, the QTP.